Gene therapy rescues cone function in an all-cone retina mouse model with the most common cone opsin C203R missense mutation - Marion E. Cahill; Kathryn Chmelik; Brooke A. Brothers; Madyson E. Ashcraft; Tongju Guan; Artjola Puja; Yinxiao Xiang; Lee M. Shaw; Jianhai Du; Wen-Tao Deng (PLoS ONE, 2026)
Blue cone monochromacy (BCM) is an X-linked cone dystrophy characterized by loss of long- (L) and medium-wavelength (M) cone function. A common cause is the C203R missense mutation, which occurs in both OPN1LW and OPN1MW , or in hybrid OPN1LW/OPN1MW opsin genes. Because BCM primarily affects foveal cones, we generated Opn1mw C198R /Opn1sw -/- /Nrl -/- ( C198RAC ) mice carrying the murine equivalent of the human C203R mutation on an all-cone retinal background. C198RAC mice exhibited absent photopic ERG responses and significantly shortened cone outer segments, recapitulating foveal cone deficits in BCM. Metabolomic profiling further revealed altered retinal metabolism, including reduced cGMP and elevated oxidative stress–related metabolites. To evaluate therapy, we delivered AAV8-Y733F expressing human L-opsin (OPN1LW) cDNA under the cone-specific PR2.1 promoter at 1 and 5 months of age. Treatment restored cone function, regenerated outer segment structures, and provided rescue for at least 5 months post-injection in both early- and late-treatment groups. These results demonstrate that densely packed cones expressing only the C198R mutant opsin remain viable targets for gene therapy. Together, this study establishes the C198RAC mouse as a cone-rich model mimicking foveal cone conditions in BCM and provides compelling preclinical evidence that AAV-mediated gene augmentation can rescue cone outer segment structure and function, supporting the feasibility of gene therapy for BCM.